2014
DOI: 10.1016/j.physio.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to providing undergraduate physiotherapy clinical education in the primary care setting: a three-round Delphi study

Abstract: This study revealed that there is support for the provision of physiotherapy clinical education in the primary care setting. Through careful consideration with clear planning and collaboration with all stakeholders, it may be possible to convert the main barriers identified into facilitators to ensure that there will be an adequately prepared physiotherapy work force in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 10 publications
1
34
0
5
Order By: Relevance
“…The ongoing communication between the academic institution and the clinical placement area offers an enabling environment for students' clinical education. [26] The clinical supervisors in this study were challenged by their perception of students, who they believed were not playing a pivotal active role in their learning and placed gratuitous pressure and demands on the supervisors.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The ongoing communication between the academic institution and the clinical placement area offers an enabling environment for students' clinical education. [26] The clinical supervisors in this study were challenged by their perception of students, who they believed were not playing a pivotal active role in their learning and placed gratuitous pressure and demands on the supervisors.…”
Section: Discussionmentioning
confidence: 87%
“…A study in Ireland on barriers and facilitators to a physiotherapy education approach supported collaboration between all stakeholders in the education framework, which facilitated learning and contributed to adequately prepared students. [26] According to Lo et al, [27] the partnership and working together of the healthcare student and the clinical supervisor are essential to offer an environment of effective learning of technical skills, core competencies and ethical and social integration into clinical practice. Furthermore, Olsen et al [28] indicated that clinical supervisors are role models and responsible for the students in clinical placement areas; they are also the main information source for students.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rural areas of Australia remain critically lacking in local physiotherapy services when compared to metropolitan areas. 31,32 Where physiotherapy positions do exist, recruitment and retention of physiotherapists remains a significant issue. 31 Additional support may also be required by clinical supervisors in rural and remote areas, as this has been identified to be a facilitating factor in clinicians supervising students.…”
Section: (1)mentioning
confidence: 99%
“…Clinical educators are generally responsible for facilitating the acquisition of profession-specific skills by student during the practical sessions and on-field training. During this time, the relationship between the clinical educator and student is considered fundamental to the success of the clinical training program [4,5]. According to the results of this study, the participant's believed that personal and professional characteristics of clinical educators such as: the ability to transfer skills to students, responsibility, having high clinical skill and professional ethics are effective factors in clinical training.…”
Section: Discussionmentioning
confidence: 91%
“…Studying a Bachelor degree in physiotherapy enables the students to participate in different clinical fields. Nowadays, developing a high-quality clinical education program to fulfill students' needs is getting tougher [4,5].…”
Section: Introductionmentioning
confidence: 99%